Lieu, genre et mémoire orale : l’histoire oubliée de l’arrivée des maquis au Val d’Aran vécue et racontée par les femmes - Mireia Boya-Busquet; Rosa Cerarols-Ramirez (Revue de Géographie Alpine)
In the Aran Valley, the political and administrative border does not coincide with the cultural boundaries. The Spanish Valley situated in the Atlantic Pyrenees and within the Occitan cultural realm has a peripheral and quite inaccessible location in relation to Spain, while it has easy access from the French side. The particularities of this territory where highly valued by the Spanish Republican army to design the Spanish Reconquest campaign during the early years of Franco’s dictatorship. The invasion of the Aran Valley is one of the historical episodes of the Spanish post-war that is has been less studied. It was the most serious attempt, in October of 1944, of establishing a provisional Republican government in the Aran Valley with the support of the Spanish guerrilla (the maquis), who also have been collaborating in the exile with the French resistance in southern France. The operation lasted 11 days and the maquis’ presence had been particularly important in this area. Its unexpected arrival and their contact with the local population are the subject of our research. This historical episode always has been explained from the point of view of the “maquis” or the francoist soldiers who participated in the operation, but never from the viewpoint of the valley residents. Our focus is to unfold the narratives of those who experienced a real alteration of their everyday life, an more particularly women. Recorded interviews are the methodological tools used to discover, to value and to preserve the oral memory of this event, always with a gender perspective. The analysis of these life’s stories of these women that were children at that time offers us a new narrative of the events, as well as a resource to understand the daily relationships and their particular sense of place. The objective and contribution of this research is thus the recollection of testimonies of the immaterial patrimony and the study of everyday life practices from a gender point of view in a key historical moment of the valley history. The importance of the recovery of the oral historical memory goes together with the breaking off of secrets around the post-war and the Spanish democratic transition.